Inverse Vulcanization of a Natural Monoene with Sulfur as Sustainable Electrochemically Active Materials for Lithium-Sulfur Batteries - Jian Xiao (MDPI AG, 2021)
A novel soluble copolymer poly(S-MVT) was synthesized using a relatively quick one-pot solvent-free method, inverse vulcanization. Both of the two raw materials are sustainable, i.e., elemental sulfur is a by-product of the petroleum industry and 4-Methyl-5-vinylthiazole (MVT) is a natural monoene compound. The microstructure of poly(S-MVT) was characterized by FT-IR, 1H NMR, XPS spectroscopy, XRD, DSC SEM, and TEM. Test results indicated that the copolymers possess protonated thiazole nitrogen atoms, meso/macroporous structure, and solubility in tetrahydrofuran and chloroform. Moreover, the improved electronic properties of poly(S-MVT) relative to elemental sulfur have also been investigated by density functional theory (DFT) calculations. The copolymers are utilized successfully as the cathode active material in Li-S batteries. Upon employment, the copolymer with 15% MVT content provided good cycling stability at a capacity of ∼514 mA h g−1 (based on the mass of copolymer) and high Coulombic efficiencies (∼100%) over 100 cycles, as well as great rate performance.